The market for acquiring card payments from small and medium-sized Canadian merchants - Angelika Welte; Jozsef Molnar (Bank of Canada, 2020)
This note uses industry data and a unique dataset of small and medium-sized merchants to provide insights into the acquirer-merchant market in Canada. Three main findings are presented. First, smaller merchants pay their acquirer more for every dollar of card payment than larger merchants. Second, this finding is mainly explained by high fixed costs. Third, the acquiring market in Canada is concentrated and has remained fairly stable since 2010.
Keywords: C; C2; D; D2; E; E4; E42; 330; Financial services; Market structure and pricing; Payment clearing and settlement systems